USAHA PENGEMBANGAN EKONOMI KREATIF, INOVATIF DAN RAMAH LINGKUNGAN BERBASIS LIMBAH MINYAK GORENG SEBAGAI GREEN SOUVENIR - Misrahanum, Misrahanum; Sadli, Sadli; Murniana, Murniana; Putra, Ferry Syah; Rezeki, Rena Novita; Muslem, Abdul Halim (Reswara: Jurnal Pengabdian Kepada Masyarakat, 2023)
Global warming has an impact on the decline in the quality of human life, as a result of the decline in the quality of the environment. To prevent and overcome these problems, an effort is needed, one of which is to produce an environmentally friendly product. Investment in environmentally friendly products is becoming an interesting trend as an effort to develop and use environmentally friendly products, one of which is green souvenirs. Green souvenirs can be a product solution to promote an environmentally friendly lifestyle with innovative products that come from the waste of daily living activities. One of them is used cooking oil. This product-based community service activity was carried out in Kayee Lee, Aceh Besar. This activity aims to produce green souvenir products. Education and promotion of environmentally friendly lifestyles for the community contribute to improving the quality of the environment. Activities that have been carried out in the form of socialization, and technical training in the process of making green souvenirs. The results of the service of the partner group have an understanding of the benefits of processing used cooking oil into green souvenirs. The training activities that have been carried out have produced green souvenir products in very varied shapes, colors, and motifs with an attractive appearance so that they are economically viable. Green souvenir product motifs can be customized for events such as seminars, graduations, birthdays, weddings, and decorative or household purposes. Green souvenir products that are expected to open up opportunities for business partners to increase family income also contribute to the environment and health.Â